Detection of Mitral Valve Diseases by Bicoherence Analysis of Heart Sound Signals - AKGÜN, ÖMER (OFFICE SPECTROSCOPY & SPECTRAL ANALYSIS, 2017)
The analysis of 10 normal and 51 mitral valve pathology making a total of 61 heart sound signals that were obtained with Littmann 4100 Digital Stethoscope were conducted in this study. Following the recorded sound signals were denoised by using wavelet filters, the signals were applied bicoherence analysis that is an high order spectral analysis method. It has been demonstrated that varieties of mitral valve pathology could be determined by three-dimensional surfaces of bicoherence and maximum bicoherence values.
Keywords: Mitral valve; Heart sound signals; Bicoherence analysis